Wound Botulism in Black Tar Heroin Injecting Users: A Case Series. (July 2021) - Raza, Nadia; Dhital, Sandhya; Espinoza, Valerie Elise; Jariwal, Roopam; Chiu, Chien-Wai; Valdez, Michael; Heidari, Arash; Petersen, Greti; Sabetian, Katayoun
The incidence of wound botulism in injection drug users has increased since the introduction of black tar heroin. Many species of the Clostridium genus, most commonly Clostridium botulinum, Clostridium baratii, and Clostridium butyricum, have been associated with wound botulism. Patients often present with progressive bulbar weakness, including dysphagia, cranial nerve palsies, and loss of speech, in addition to symmetrical descending weakness of the upper extremities that may progress to the chest and lower extremities. In this article, we present 3 cases of wound botulism, in which the patients presented with bulbar weakness and were treated with botulism antitoxin heptavalent. The time to antitoxin administration and its effect on the patients' clinical courses is compared.